2003
DOI: 10.1287/orsc.14.3.264.15163
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Gears, Shifting Niches: Organizational Inertia and Change in the Evolution of the U.S. Automobile Industry, 1885–1981

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
3
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 54 publications
6
97
3
2
Order By: Relevance
“…However, this is not the case among voluntary associations (competition does, however, curb membership growth (Wollebaek & Selle, 2006)). With regard to change, it should be extremely difficult to undertake fundamental change in an old and established organization (Amburgey, Kelly, & Barnett, 1993;Dobrev, Kim, & Carroll, 2003;Halliday, Powell, & Granfors, 1993;Kelly & Amburgey, 1991;Miller & Chen, 1994;Tushman & Anderson, 1986). But in our material, old organizations change more often than young groups.…”
Section: How? the Dynamics Of Changementioning
confidence: 99%
“…However, this is not the case among voluntary associations (competition does, however, curb membership growth (Wollebaek & Selle, 2006)). With regard to change, it should be extremely difficult to undertake fundamental change in an old and established organization (Amburgey, Kelly, & Barnett, 1993;Dobrev, Kim, & Carroll, 2003;Halliday, Powell, & Granfors, 1993;Kelly & Amburgey, 1991;Miller & Chen, 1994;Tushman & Anderson, 1986). But in our material, old organizations change more often than young groups.…”
Section: How? the Dynamics Of Changementioning
confidence: 99%
“…Barnett and Carroll (1995) suggested that core structural change can be defined in terms of the extensiveness of the concurrent and subsequent changes that are related to an initial transformation. Cascades of associated but unforeseen disruptions to routines and procedures throughout firms may be the primary cause of the observed spikes in failure rates associated with organizational change more generally (Amburgey et al, 1993;Dobrev et al, 2003). It is worth reiterating the distinction between buffering mechanisms meant to insulate a firm from the need for transformation in the first place, and shielding mechanisms that protect the firm from the deleterious effects of a given transformation (Miner et al, 1990).…”
Section: Figure 2 Effect Of Ceo Ownership By Venture Capitalist Ownermentioning
confidence: 99%
“…Using theoretical perspectives drawn primarily from organizational ecology (e.g., Barnett & Carroll, 1995;Hannan & Freeman, 1984), researchers have attempted to differentiate "core" from "peripheral" change, arguing that changes to four structural features-mission, authority structure, technology, and marketing strategy-are those most likely to reset the liability of newness clock. This approach is somewhat limiting, however, as what constitutes a core or peripheral change, as well as its degree of criticality, can vary among firms and populations (Aldrich, 1999;Dobrev, Kim, & Carroll, 2003). Aldrich (1999) suggested an alternative, nonordinal set of criteria for evaluating the degree to which a given event constitutes a significant transformation.…”
mentioning
confidence: 99%
“…The influence of organizational social dynamics, including enablers and inhibitors like momentum and inertia, are frequently underestimated and overlooked (Dobrev et al 2003;Slaughter 1999). Momentum is an energy level driving change activities, coupled with the rate at which change is happening, while inertia relates to forces that reduce momentum and move an organization toward stagnation, mediocrity, rigidity, and entropy (D'Aveni et al 2010;De Pree 2004;Doz and Kosonen 2008).…”
Section: Part IV Social Dynamicsmentioning
confidence: 99%